Halal Industrial Village Assistance and Signing Cooperation Agreement With Batu Gadang Village - Aisman, Aisman; Rini, Rini; Hasbullah, Hasbullah; Sylvi, Diana; Hari, Purnama Dini; Ismed, Ismed; Refdi, Cesar Welya; Wellyalina, Wellyalina; Rasdiana, Felga Zulfia; Koja, Reni; Nova, Bastian; Wati, Linda (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
This community service activity carried out by the Faculty of Agricultural Technology, Andalas University, Padang, is in collaboration with the Batu Gadang Village, Lubuk Kilangan District, Padang City. The activity location is in the Batu Gadang (Indarung) Lurah Office which has been prepared in such a good way, in the Batu Gadang Village there are still MSMEs that do not have halal certification and have the potential to be used as a model for a halal food industry village in West Sumatra. The main problem encountered is the lack of information received by MSME actors in the Batu Gadang Village to obtain halal certificates. Therefore, it is necessary to provide assistance to MSME actors in the Batu Gadang sub-district from the beginning until the issuance of the halal certificate